Numerical Optimization Method of Spacecraft Antenna Retargeting Point Calculations - Sukhodoev M. S. Mikhail Sergeevich; Savenko I. I. Igor Igorevich; Skirnevsky I. P. Igor Petrovich; Loginov D. A. (Mechatronics, Automation and Control, 2015)
Title screen